2011
DOI: 10.1590/s0103-50532011000900008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on methylene blue decolorization in aqueous medium in electrical discharge plasma reactor

Abstract: Este estudo investigou o efeito da temperatura da solução sobre a descoloração do azul de metileno em um reator de plasma de descarga elétrica do tipo ponta-plano. Os resultados mostraram um aumento da porcentagem inicial de descoloração do corante com o aumento da temperatura da solução de 4 para 28 o C, mas de 28 para 37 o C não houve alteração. Entretanto, quando a temperatura foi elevada para 47 o C a porcentagem de descoloração inicial do corante diminuiu. A formação de peróxido de hidrogênio em água dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 24 publications
5
28
0
Order By: Relevance
“…Where the temperature required to the maximum rate of color removal tends to correspond with the optimum bacterial growth tempera- ture of 30°C (60.3%). This result is in concordant with Benetoli et al (2011). While Liu et al (2014) suggested that the maximum dye removal is achieved at 40°C.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Where the temperature required to the maximum rate of color removal tends to correspond with the optimum bacterial growth tempera- ture of 30°C (60.3%). This result is in concordant with Benetoli et al (2011). While Liu et al (2014) suggested that the maximum dye removal is achieved at 40°C.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, much higher temperatures also weaken the decolorization, which may be due to inactivation of intracellular enzymes assisting in the active transport of the bacteria, reducing the bacterial activity. Appropriately, raising the temperature could enhance the bacterial adsorption activity, thereby improving the decolorization efficiency (Benetoli et al 2011). Bacterial culture generally exhibits maximum decolorization at pH 5 (59.6%) whereas the rate of color removal tends to decrease rapidly at highly acidic or alkaline pH.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the induced chemistry in such a medium is very wide, and many other species that can contribute to MB degradation can be produced. For instance, water temperature increases significantly (to ~70 °C), and it has been observed, by Benetoli et al [37], that dye decolorization increased with an increase in solution temperature. Also, other oxidizing species, such as peroxonitrous acid (ONOOH), can be produced in our conditions (e.g., H + + NO2‾ + H2O2 → ONOOH + H2O) and can contribute to MB degradation [38].…”
Section: Fig 12 Normalized Absorbance For Mb With Respect To the Purmentioning
confidence: 91%
“…One of the most interesting topics, in recent years, has been studying degradation of different materials in aqueous solution such as degradation of methyl orange [18], methyl violet [19], phenol [20], methanol [21], diuron [22], 1-naphthylamine [23], pharmaceutical compound pentoxifylline [24], organophosphate pesticides [25], antibiotics [26], textile dyes [27], etc. In such studies, scientists are interested in investigating the effects of various parameters such as pH [28] and temperature [29] on the plasma-treatment process. The degradation process of some materials such as bromophenol blue during plasma irradiation has not been investigated; some studies concerned the degradation of bromophenol blue without using plasma irradiation [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%